ANOMALIES IN CIRRHINUS MRIGALA, A COMMERCIALLY IMPORTANT FRESHWATER FOOD FISH, FROM GURDASPUR DISTRICT OF PUNJAB - S. P. S. DUTTA,; D. SLATHIA,; G. CHANDER,; H. KUMAR, (The Bioscan, 2011)
Cirrhinus mrigala, an important Indian major carp and commonly known as Mrigal, is widely distributed in Indian lotic and lentic water bodies and is cultured in ponds in various Indian states. During the survey of deformed fishes, eight specimens of Cirrhinus mrigala, brought and reared in some fish ponds of Gurdaspur district of Punjab were seen at Gumat fish market, Jammu, and have been described for various morphological and vertebral deformities. The deformities, as noticed in the aberrant fish specimens of Cirrhinus mrigala are generally post dorsal and are most probably induced by excessive use of pesticides in agricultural fields in the area resulting in surface and ground water contamination.